L’histoire d’un vrai faux traité philosophique (Ḥatatā Zar’a Yā‘eqob et Ḥatatā Walda Ḥeywat). Épisode 1 : Le temps de la découverte. De l’entrée en collection à l’édition scientifique (1852-1904) - Anaïs Wion (Afriques)
On the Ethiopian highlands in the middle of the 19th century, Juste d’Urbin, a Catholic missionary, chose to stop evangelizing and devote himself fully to the study of the Ge’ez and Amharic languages and of the country’s Orthodox civilization. He sent to his mentor, Antoine d’Abbadie (well-known at the time for his writings on Ethiopia) his work, in particular two copies of a very rare philosophical text presumably authored by an Ethiopian in the 17th century. This first article in a series devoted to the history of Ḥatatā Zar’a Yā‘eqob and its appendix, Ḥatatā Walda Ḥeywat, shows how these texts fit into Juste d’Urbin’s work, describes the manuscripts he sent to Antoine d’Abbadie, and analyzes the hitherto unpublished correspondence between these two men.  Juste d’Urbin, a linguist and translator, wanted to make a contribution to Ethiopian studies. His letters reveal an ambitious, anxious thinker who wanted to realize a work of philosophy. Might the two Ḥatatā have been a response to this twofold ambition?